( | 4 | x | + | 2 | ) | ÷ | 6 | − | ( | 10 | x | + | 1 | ) | ÷ | 6 | = | 1 |
Left side of the equation = | 4 | x | × | 1 6 | + | 2 | × | 1 6 | − | ( | 10 | x | + | 1 | ) | × | 1 6 |
= | 2 3 | x | + | 1 3 | − | ( | 10 | x | + | 1 | ) | × | 1 6 |
= | 2 3 | x | + | 1 3 | − | 10 | x | × | 1 6 | − | 1 | × | 1 6 |
= | 2 3 | x | + | 1 3 | − | 5 3 | x | − | 1 6 |
= | - | 1 | x | + | 1 6 |
- | 1 | x | + | 1 6 | = | 1 |
- | 1 | x | = | 1 | − | 1 6 |
- | x | = | 1 | − | 1 6 |
- | x | = | 5 6 |
- | 5 6 | = | x |
x | = | - | 5 6 |